1997
DOI: 10.1063/1.531814
|View full text |Cite
|
Sign up to set email alerts
|

On quantum field theory with nonzero minimal uncertainties in positions and momenta

Abstract: A noncommutative geometric generalisation of the quantum field theoretical framework is developed by generalising the Heisenberg commutation relations. There appear nonzero minimal uncertainties in positions and in momenta. As the main result it is shown with the example of a quadratically ultraviolet divergent graph in φ 4 theory that nonzero minimal uncertainties in positions do have the power to regularise. These studies are motivated with the ansatz that nonzero minimal uncertainties in positions and in mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
191
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(202 citation statements)
references
References 51 publications
7
191
0
3
Order By: Relevance
“…For example, the ultraviolet regularity of loop graphs in such field theories has been shown. See [28,29,30]. In work by Brout et al, [11], it has been shown that this type of short-distance cut-off without energy-momentum cut-off, when built into quantum theory could resolve the transplanckian energies paradox of black hole radiation -without invoking superoscillations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the ultraviolet regularity of loop graphs in such field theories has been shown. See [28,29,30]. In work by Brout et al, [11], it has been shown that this type of short-distance cut-off without energy-momentum cut-off, when built into quantum theory could resolve the transplanckian energies paradox of black hole radiation -without invoking superoscillations.…”
Section: Discussionmentioning
confidence: 99%
“…These predictions motivated several authors to search for model independent arguments, leading to the same conclusions as string theory does (we refer to [16] for a survey on the subject). In particular it has been shown that the above results can be reproduced on a purely kinematical level with appropriate deformations of the Heisenberg commutation relations [49,40,33,1], i.e., of canonical quantum statistics. In all such cases the coordinates do not commute at small distances, a result which is consistent with the spirit of non-commutative geometry [7].…”
Section: Introductionmentioning
confidence: 82%
“…The formalism, based on this deformed algebra, together with the new concepts it implies, has been discussed extensively in one and more dimensions by Kempf and co-workers in Refs. [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%